Analysis of postpartum intrauterine contraceptive devices - Shrigadhi, Sandhya A.; Gawandi, Prabhakar S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: PPIUCDs are the only postpartum family planning method for couples requesting a highly effective and reversible, yet long acting, family planning method that can be initiated during the immediate postpartum in lactating women. The public health benefits from PPIUCDs stemmed from the women’s increased accessibility to PPIUCDs following facility births, as PPIUCDs could be offered at health facilities after childbirth. It is an attempt to reduce unmet family planning need. The specific aims of this study were to assess the acceptability, feasibility expulsion rate and complications of PPIUCD insertion among women delivering at term in our institute who were eligible and counselled for PPIUCD. Methods: Prospective study undertaken at Dr. Vaishampayan memorial government medical college, Solapur, Maharashtra conducted from September 2015 to August 2017. All women undergoing delivery at term in this institute and not having any contraindications for postpartum IUCD insertion were counseled for PPIUCD. Results: A total 3032 were eligible for PPIUCD insertion and were counseled for the same. 1.97% women accepted PPIUCD insertion while 98.03% of them declined insertion. 1124 underwent caesarean section while 1908 had vaginal delivery. Among vaginal delivery group rate of acceptance was 1.20% while that in caesarean section group was 3.29%. Conclusions: The present study concluded that overall acceptance of PPIUCD in our institute is 1.97 %. Considering fear of complications related to IUCD and partner refusal as major causes of refusal for PPIUCD in our study, emphasis on this aspect during counseling can improve acceptance.